Small Molecules Targeting HATs, HDACs, and BRDs in Cancer Therapy - Wu, Donglu; Qiu, Ye; Jiao, Yunshuang; Qiu, Zhidong; Liu, Da (Frontiers in Oncology, 2020)
Evidence for research over the past decade shows that epigenetic regulation mechanisms run through the development and prognosis of tumors. Therefore, small molecular compounds targeting epigenetic regulation have become a research hotspot in the development of cancer therapeutic drugs. According to the obvious abnormality of histone acetylation when tumors occur, it suggests that histone acetylation modification plays an important role in the process of tumorigenesis. Currently, as a new potential anti-cancer therapeutic drugs, many active small molecules that target histone acetylation regulatory enzymes or proteins such as histone deacetylases (HDACs), histone acetyltransferase (HATs) and bromodomains (BRDs) have been developed to restore abnormal histone acetylation levels to normal. In this review, we will focus on summarizing the changes of histone acetylation levels during tumorigenesis, as well as the possible pharmacological mechanisms of small molecules that target histone acetylation in cancer treatment.